Synthesis and In Vitro Profiling of Psilocin Derivatives : Improved Stability and Synthetic Properties - Eklund, Julia; Bremberg, Ulf; Larsson, Jessica; Torkelsson, Edvard; Wennerberg, Johan; Zandelin, Symantha; Odell, Luke R. (Journal of Medicinal Chemistry, 2025)
As interest in using psilocybin therapy for treating mental health disorders intensifies, the need for efficient production methods becomes increasingly important. Current medical-grade psilocybin production is inefficient and relies on a complicated multistep synthesis. This study has explored and evaluated psilocin ester prodrugs and psilocin salts as potential alternatives to psilocybin, focusing on their ease of synthesis, chemical stability, and metabolic profiles. A diverse library of 15 psilocin ester prodrugs and six psilocin salts was synthesized and evaluated. The study successfully identified several psilocin ester prodrugs and psilocin salts that exhibited desirable characteristics, including storage and handling stability, rapid metabolic conversion to psilocin, and easy synthesis, with potential advantages over psilocybin. This research introduces viable options through psilocin ester compounds and psilocin salts, offering promising avenues for future development.